2023
DOI: 10.3390/app13053037
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint-Based Localization Approach for WSN Using Machine Learning Models

Abstract: The area of localization in wireless sensor networks (WSNs) has received considerable attention recently, driven by the need to develop an accurate localization system with the minimum cost and energy consumption possible. On the other hand, machine learning (ML) algorithms have been employed widely in several WSN-based applications (data gathering, clustering, energy-harvesting, and node localization) and showed an enhancement in the obtained results. In this paper, an efficient WSN-based fingerprinting local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In general, CNN architecture requires a large dataset for training purposes in order to achieve better classification performance, which is not valid in the area of plant disease classification. In addition, when the number of model parameters exceeds the number of data samples, the small training dataset causes overfitting, and hence minimize the classification accuracy 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, CNN architecture requires a large dataset for training purposes in order to achieve better classification performance, which is not valid in the area of plant disease classification. In addition, when the number of model parameters exceeds the number of data samples, the small training dataset causes overfitting, and hence minimize the classification accuracy 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results presented in [ 16 ] may be affected by the use of an inaccurate path loss model that differs from actual signal attenuation in a real environment. In comparison, [ 17 ] should not have such flaws, since it was based on measurements of signal levels from Xbee modems in a real indoor environment. The authors did not specify in which ISM band the modems operated, but four neural network structures were examined: linear regression, random forest, K-nearest neighbor and decision tree, and the article includes a comparison of their position estimation accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…They concluded that the proposed algorithm had two advantages over traditional tracking methods: The first was refining the sampling method by thus reducing the frequency of the sampling. The second reason was the dynamic updating of the fingerprints [ 5 , 12 , 49 ]. Qian et al [ 20 ] proposed using CSI to detect moving targets, and their results indicated that in comparison to the previous approaches, their proposed approach is more robust and more accurate.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Usually, the radio transmitter (TX) broadcasts a signal within a network, and the target reflects the propagating signal [ 9 , 10 , 11 ]. When the signal is received by the receiver (RX), it can be used to estimate a target’s location [ 12 , 13 , 14 , 15 ]. Different techniques can be used for target tracking, which include the angle of arrival (AOA), received signal strength indicators (RSSI), the time-of-arrival (TOA), as well as the time difference of arrival (TDOA) [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%